(untitled) (Applied Biological Research, 2025)
Cinnamomum zeylanicum Blume (Lauraceae) bark is one of the most important spices used to enhance the taste and flavour of Indian foods. Besides its use as a spice, C. zeylanicum bark possesses antioxidant, antimicrobial, antifungal, anti-inflammatory, and chemoprotective properties. The present study aimed to characterize the key chemical constituents of C. zeylanicum bark essential oil and to determine its chemoprotective effect against triple-negative breast cancer (TNBC) cells. The chemical composition of C. zeylanicum bark essential oil was determined using gas chromatography–mass spectrometry (GC–MS). The analysis identified 29 chemical compounds, among which (E)-cinnamaldehyde (69.89%), eugenol (14.27%), δ-cadinene (2.80%), and (Z)-caryophyllene (2.33%) were the major constituents. The essential oil exhibited concentration- and time-dependent inhibition of TNBC (MDA-MB-231) cells. A concentration of 15.62 μL mL⁻¹ produced maximum inhibition of MDA-MB-231 cells, amounting to approximately 90.6%. The aroma profile and significant in vitro anticancer activity of C. zeylanicum bark essential oil provide a scientific basis for its potential use as a cancer remedy